Twenty-five years of international exchanges of plant genetic resources facilitated by the CGIAR genebanks: a case study on global interdependence - Galluzzi, Gea; Halewood, Michael; López Noriega, Isabel; Vernooy, Ronnie (Springer, 2016)
This article analyses 25 years of data about international movements of plant genetic resources for food and agriculture (PGRFA), facilitated by the gene banks hosted by seven centres of the Consultative Group on International Agricultural Research. It identifies trends in the movements of PGRFA for use in research and development, and describes the diversity of those resources transferred over time. The paper also presents data on the number of countries involved in the global exchanges, analyses their development status and describes their role as providers and/or recipients, providing a picture of the breadth of these global exchanges. We highlight that it is primarily developing and transition economies that have participated in the flows, and that the transferred germplasm has been largely used within their public agricultural research and development programmes. We conclude that, when provided the opportunity of facilitated access, countries will use a wide diversity of germplasm from many other countries, sub-regions and continents as inputs into their agricultural research and development programmes. We highlight the importance of enabling the continuation of the non-monetary benefits from international access to germplasm. We discuss the implications for the process of development and reform of the multilateral system of access and benefit sharing under International Treaty on Plant Genetic Resources for Food and Agriculture.